1990
DOI: 10.1159/000177590
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status of Ambulatory and Nonambulatory Mentally Retarded Children with and without Carbamazepine Treatment

Abstract: The subjects consisted of four groups: group 1 nonambulatory patients receiving carbamazepine; group 2 ambulatory patients receiving carbamazepine; group 3 nonambulatory patients receiving no drug, and group 4 ambulatory patients receiving no drugs. The serum 25-hydroxyvitamin D (25-OH-D) concentration was significantly lower in group 1 than in all other groups. There was no difference between the groups as regards the serum 1,25-dihydroxyvitamin D or 24,25-dihydroxyvitamin D concentration. Carbamazepine treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

1993
1993
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 20 publications
0
8
0
2
Order By: Relevance
“…Clinical trials have examined the association between vitamin D and mental retardation, depression, autism and behavioral disorders in children and adults . Smith et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical trials have examined the association between vitamin D and mental retardation, depression, autism and behavioral disorders in children and adults . Smith et al .…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials have examined the association between vitamin D and mental retardation, depression, autism and behavioral disorders in children and adults. 16,[35][36][37] Smith et al found that vitamin D insufficiency is common in children with cystic fibrosis. 37 Mostafa and Al-Ayadhi suggested that autistic children had significantly lower serum 25-OH-vitamin D than healthy children.…”
Section: Discussionmentioning
confidence: 99%
“…This in turn would lead to increased PTH, which would lead to increases in bone turnover, with subsequent bone loss. A considerable number of studies have found decreased 25‐(OH)D levels in patients treated with CBZ relative to controls or patients taking a noninducing AED (Tjellesen & Christiansen, 1982; Hoikka et al., 1984; Gough et al., 1986; Lamberg‐Allardt et al., 1990; Mintzer et al., 2006; Kim et al., 2007). Interestingly, several studies do not consistently find significantly reduced serum vitamin D levels, and findings regarding serum calcium and PTH levels also are not consistent.…”
Section: Discussionmentioning
confidence: 99%
“…The capsid gene was also highly divergent, with only 31% translated amino acid identity over 17% of the gene to the corresponding capsid gene in goose parvovirus (ACK86566.1). Sequences encoding a conserved P-loop nucleoside triphosphate (NTP)-binding domain (50) and N-terminal parvovirus coat domain (51) were detected in the replicase and capsid genes, respectively. The capsid gene also encoded a putative phospholipase A 2 (PLA 2 ) motif that is critical for parvovirus infectivity (52).…”
Section: Discovery Of Phv In Seronegative Hepatitis and Diarrheal Sammentioning
confidence: 99%